Nilai-Nilai Kearifan Lokal pada Lakon Baruklinting dalam Wayang Timplong sebagai Norma Bermasyarakat - Yatmin, Yatmin; Enda, Tita Nur (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study is motivated by observations of the potential found in Nganjuk Regency, particularly the Wayang Timplong. Wayang Timplong contains many performances that encapsulate local wisdom, one of which is the Baruklinting play. In light of the growing moral degradation phenomena, applying local wisdom values within social norms is an effective approach to addressing these issues. The aim of this research is to explore the history of Wayang Timplong, the storyline of Baruklinting, and the local wisdom embedded in the Baruklinting play within Wayang Timplong. This research uses a qualitative ethnographic method with data collection techniques including interviews, observation, and documentation studies. The results reveal the internalization of local wisdom values from the Baruklinting play in Wayang Timplong as moral and social norms. The conclusion highlights that the art of Wayang Timplong carries important local wisdom values, essential for fostering social relations and strengthening local cultural identity.